ANALISIS PENERAPAN APLIKASI OVO MENGGUNAKAN MODEL UTAUT 3 PADA PENGGUNA - Romadona Putra, Diska; Supelti, Diana; Yusuf, Abdul (IKIP PGRI Bojonegoro, 2022)
Abstract: The development of fintech in Indonesia is getting higher because it can facilitate transactions made by humans. OVO is one of the digital payments that is developing in Indonesia. This research was conducted to find out how the public's acceptance of the OVO application by testing the phenomenon using the UTAUT 3 research model. This study used quantitative data analysis in the form of path analysis using SmartPLS software. As for this study, researchers distributed questionnaires and got 56 respondents. The population of this study were users of the OVO application and the sampling technique used simple random sampling and then 56 respondents were obtained. The results of this study found that facilitating conditions, hedonic motivation and habits have a significant influence on behavioral intentions. Then habits and behavioral intentions were found to have a significant influence on usage behavior. Hedonic motivation is the only variable that has an indirect effect on usage behavior through behavioral intentions.Keywords: Fintech; Digital Payment; UTAUT 3; OVO; SmartPLS